Adopting, Networking, and Communicating on Twitter: A Cross-National Comparative Analysis. (December 2017) - Vergeer, Maurice
Twitter is one of the most popular online social network platforms for political communication. This study explains how political candidates in five countries increase their online popularity and visibility by their behavior on Twitter. Also, the study focuses on cultural differences in online social relations by comparing political candidates in five countries in the East and West: South Korea, Japan, United Kingdom, Canada, and the Netherlands. Findings show that signing up to Twitter as early as possible increases one's online popularity as predicted by the process of preferential attachment. Candidates actively following citizens and sending undirected tweets also increases the group of followers. This doesn't apply however to conversational tweets, which decreases the number of a candidate's followers slightly. South Korea, having a collectivistic culture, shows higher levels of reciprocity on Twitter, although this does not increase the group of followers. In other countries, including collectivistic Japan, candidates reciprocate less frequently with citizens, effectively using Twitter more as a mass medium for broadcasting.